2012
DOI: 10.1111/j.1096-3642.2012.00832.x
|View full text |Cite
|
Sign up to set email alerts
|

The phylogeny of a reduced ‘sand goby’ group based on behavioural and life history characters

Abstract: Phylogenetic analysis of 27 behavioural and life history traits for five Mediterranean sand goby species (Perciformes, Gobiidae) produced one tree with a consistency index (excluding uninformative characters) of 0.756. This tree agreed with previous molecular analyses in providing strong support for the monophyly of the sand gobies, indicating that Pomatoschistus and Knipowitschia are paraphyletic and helping to resolve the ambiguous position of Economidichthys pygmaeus, placing it as the basal member of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 56 publications
1
20
0
5
Order By: Relevance
“…Malavasi et al . () used behavioural and life history data to build a phylogeny for the European gobiid lineages and Kramer et al . () studied the potential for teeth to inform phylogenetic relationships of European gobiids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malavasi et al . () used behavioural and life history data to build a phylogeny for the European gobiid lineages and Kramer et al . () studied the potential for teeth to inform phylogenetic relationships of European gobiids.…”
Section: Introductionmentioning
confidence: 99%
“…Simonović (1999) studied the relationship between Ponto-Caspian and Atlantic-Mediterranean gobies using external morphological, osteological and karyological data. Malavasi et al (2012) used behavioural and life history data to build a phylogeny for the European gobiid lineages and Kramer et al (2012) studied the potential for teeth to inform phylogenetic relationships of European gobiids. Gobiidae is the most species-rich fish family both in the Mediterranean Sea and among marine fishes more generally, with numbers of described gobiid species constantly increasing (Kovačić et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…P. microps and P. minutus belong to two different clades of the 'sand goby group' radiation. The divergence time of the two clades is estimated to be 2-5 Mya (Huyse et al 2004;Vanhove et al 2012) and behaviors including sound may have diverged during this time, and hence show a phylogenetic signal (Malavasi et al 2012). The two other sympatric 'sand goby group' species in shallow bays of Sweden (Kullander et al 2012), Gobiusculus flavescens (Fabricius, 1779) and P. pictus, as well as the deep water species Pomatoschistus norvegicus (Collett, 1902), appear to belong to the same clade as P. minutus.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, acoustic communication and its interaction with environmental properties and background noise have been of particular interest (Radford et al 2014;Holt and Johnston 2015). In the so called 'sand goby group' (family Gobiidae, Huyse et al 2004), at least eight species have been shown to produce low frequency acoustic pulses in a reproductive context (Malavasi et al 2012;Bolgan et al 2013;Pedroso et al 2013;de Jong et al 2016) two-spotted goby Gobiusculus flavescens (Fabricius, 1779), Adriatic dwarf goby Knipowitschia panizzae (Verga, 1841), Italian spring goby Knipowitschia punctatissima (Canestrini, 1864) canestrini's goby Pomatoschistus c a n e s t r i n i ( N i n n i , 1 8 8 3 ) , m a r b l e d g o b y Pomatoschistus marmoratus (Risso, 1810), common goby Pomatoschistus microps (Krøyer, 1838) (one individual only), sand goby Pomatoschistus minutus (Pallas, 1770) and painted gobyPomatoschistus pictus (Malm, 1865). The functions of these sounds are still unknown, but they have been proposed to be used in male courtship and female choice (Lugli and Torricelli 1999;Lindström and Lugli 2000;Pedroso et al 2013), or in species recognition .…”
Section: Introductionmentioning
confidence: 99%
“…A comparative analysis of the sound structure within Mediterranean–Atlantic gobies showed a clear distinction between these two lineages, suggesting a good degree of congruence between acoustic affinities and phylogenetic relationships (Malavasi et al ., ). Given that the phylogeny of this group of species was probably driven by complex geological events related to separation of the Tethys and Paratethys, the Messinian salinity crisis, and the subsequent re‐flooding of the Atlantic Sea (Penzo et al ., ; Huyse, Van Houdt & Volckaert, ; Miller, ; Malavasi et al ., ; Vanhove et al ., ), the clarification of the phylogenetic relationships within these two lineages is of particular phylogeographical interest. Nevertheless, due to the systematic complexity of this group and the high number of species, a great deal of information is still required to obtain a reliable, complete picture.…”
Section: Introductionmentioning
confidence: 99%